Phytoestrogens: A Promising Therapeutic Approach for Endometriosis Management, Insights from Preclinical and Clinical Studies - Neykhonji, Marzieh; Al-Asady, Abdulridha Mohammed; Al Okla, Souad; Al-Nazwani, Nasser; Avan, Amir; Khazaei, Majid; Hassanian, Seyed Mahdi (Current Pharmaceutical Design, 2025)
IntroductionEndometriosis is a prevalent gynecological disorder characterized by the growth of endometrial tissue outside the uterine cavity. The disease often involves internal organs and leads to chronic pelvic pain and infertility. While its pathogenesis remains incompletely understood, the disease is considered estrogen-dependent, and reducing estrogen levels is a primary clinical treatment strategy. Despite extensive research and diverse treatment modalities, including surgery and pharmacotherapy, current treatments are associated with significant complications and recurrence. This review aims to explore recent studies on phytoestrogens' therapeutic potential in endometriosis treatment by examining the underlying mechanisms contributing to their efficacy.MethodsAn extensive evaluation of Google Scholar and PubMed, utilizing relevant keywords including “Endometriosis, Phytoestrogen, Estrogen, inflammation, pelvic pain, and Infertility” was carried out to assess the potential therapeutic efficacy of phytoestrogens in managing endometriosis, based on recent research findings. This review considered a wide range of studies, including in vitro, in vivo, and clinical studies, as well as reviews and research articles, to provide a comprehensive overview of the current state of knowledge on this topic.ResultsPhytoestrogens, with their structural similarity to estrogen, have emerged as a novel therapeutic approach. These compounds compete for estrogen receptor binding, displaying anti-estrogenic or weak pro-estrogenic properties upon binding.ConclusionExhibiting anti-proliferative, antioxidant, anti-angiogenic, and pro-apoptotic properties, phytoestrogens have demonstrated substantial therapeutic potential in endometriosis management. Extensive cellular, animal, and clinical investigations support their therapeutic efficacy.
Keywords: inflammation